Step * 2 of Lemma es-prior-fixedpoints-no_repeats


1. Info Type
2. es EO+(Info)
3. EClass(Top)
4. E(X) ─→ E(X)
5. ∀x:E(X). c≤ x
6. E(X)@i
7. ∀e1:E(X). ((e1 < e)  no_repeats(E(X);prior-f-fixedpoints(e1)))
8. ¬((f e) e ∈ E)
⊢ no_repeats(E(X);prior-f-fixedpoints(e))
BY
(Subst ⌈prior-f-fixedpoints(e) prior-f-fixedpoints(f**(e)) ∈ (E(X) List)⌉ 0⋅ THEN Auto) }

1
.....equality..... 
1. Info Type
2. es EO+(Info)
3. EClass(Top)
4. E(X) ─→ E(X)
5. ∀x:E(X). c≤ x
6. E(X)@i
7. ∀e1:E(X). ((e1 < e)  no_repeats(E(X);prior-f-fixedpoints(e1)))
8. ¬((f e) e ∈ E)
⊢ prior-f-fixedpoints(e) prior-f-fixedpoints(f**(e)) ∈ (E(X) List)

2
1. Info Type
2. es EO+(Info)
3. EClass(Top)
4. E(X) ─→ E(X)
5. ∀x:E(X). c≤ x
6. E(X)@i
7. ∀e1:E(X). ((e1 < e)  no_repeats(E(X);prior-f-fixedpoints(e1)))
8. ¬((f e) e ∈ E)
⊢ no_repeats(E(X);prior-f-fixedpoints(f**(e)))


Latex:



Latex:

1.  Info  :  Type
2.  es  :  EO+(Info)
3.  X  :  EClass(Top)
4.  f  :  E(X)  {}\mrightarrow{}  E(X)
5.  \mforall{}x:E(X).  f  x  c\mleq{}  x
6.  e  :  E(X)@i
7.  \mforall{}e1:E(X).  ((e1  <  e)  {}\mRightarrow{}  no\_repeats(E(X);prior-f-fixedpoints(e1)))
8.  \mneg{}((f  e)  =  e)
\mvdash{}  no\_repeats(E(X);prior-f-fixedpoints(e))


By


Latex:
(Subst  \mkleeneopen{}prior-f-fixedpoints(e)  =  prior-f-fixedpoints(f**(e))\mkleeneclose{}  0\mcdot{}  THEN  Auto)




Home Index